Formation of type ia fibre bragg gratings in germanosilicate optical fibre - Kalli, Kyriacos; Simpson, Alexander George; Zhou, Kaiming; Zhang, Lin; Bennion, Ian (My University, 2004)
A report is made that the rate at which type IA fibre Bragg gratings may be inscribed is related to the intensity of the UV inscription laser and that these gratings may be written in only a few minutes. Also presented is the model of the refractive index of type IA gratings.
Keywords: Optical fibers; Bragg gratings; Refractive index; Fiber optics